2010
DOI: 10.1111/j.1365-2044.2009.06231.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia for shoulder surgery: a critical appraisal and review of current techniques

Abstract: SummaryShoulder surgery is well recognised as having the potential to cause severe postoperative pain. The aim of this review is to assess critically the evidence relating to the effectiveness of regional anaesthesia techniques commonly used for postoperative analgesia following shoulder surgery. Subacromial ⁄ intra-articular local anaesthetic infiltration appears to perform only marginally better than placebo, and because the technique has been associated with catastrophic chondrolysis, it can no longer be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
297
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 294 publications
(305 citation statements)
references
References 99 publications
2
297
2
4
Order By: Relevance
“…The single local anaesthetic injection effectiveness for open shoulder surgery was previously poorly documented and not well defined [2,8,14], more data even if with discordant results have been reported that however were more related to the continuous infusion of anaesthetics and arthroscopic setting [5,9,[15][16][17]. Anyhow, a little clinical benefit of local infiltration was evidenced [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The single local anaesthetic injection effectiveness for open shoulder surgery was previously poorly documented and not well defined [2,8,14], more data even if with discordant results have been reported that however were more related to the continuous infusion of anaesthetics and arthroscopic setting [5,9,[15][16][17]. Anyhow, a little clinical benefit of local infiltration was evidenced [3].…”
Section: Discussionmentioning
confidence: 99%
“…Discordant results have been reported regarding local injection of anaesthetics in the intra-articular region for control of postoperative pain after shoulder surgery [3,8], similar to subacromial injection [5,9,10] and block of the suprascapular nerve [11].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations